2016
DOI: 10.4149/av_2016_03_234
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and antigenicity of a recombinant chimeric protein containing epitopes of poliovirus type 1

et al.

Abstract: Summary. -To design a vaccine that simultaneously prevents both rotavirus (RV) and poliovirus (PV), a PV type 1 (PV1) chimeric protein using RV VP6 as a vector (VP6F) was constructed, expressed in Escherichia coli expression system and characterized by SDS-PAGE, Western blot, immunofluorescence assay and neutralization test. The results showed that the chimeric protein reacted with anti-VP6F and anti-PV1 antibodies and elicited production of serum antibodies against the chimeric protein in guinea pigs. Antibod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…( A ) Different expression systems from prokaryotic E. coli [ 2 , 72 , 126 ] to eukaryotic systems such as yeast [ 17 ], insect cell/baculovirus systems (IC-BV) [ 38 , 67 ], mammalian cells [ 38 ], HSV-1 [ 90 ], and plant cells [ 37 , 89 , 127 ] have been used successfully to produce assembled structures of VP6 tubes/VLPs. ( B ) Applications of VP6 tubes/VLPs, as vaccines (immunogenicity and protection) [ 15 , 44 , 54 , 55 , 64 66 , 70 , 95 , 108 ], adjuvants [ 15 , 16 , 55 , 76 78 , 108 – 110 ], immunological carriers [ 49 , 53 , 92 , 96 , 102 , 111 ], drug delivery tools [ 5 , 91 , 122 , 126 ], and nano-biomaterials [ 5 , 23 , 24 , 41 , 42 , 50 , 91 , 122 , 126 ] …”
Section: Vp6 Expression and Formation Of Structured Vp6 Tubes/vlpsmentioning
confidence: 99%
See 1 more Smart Citation
“…( A ) Different expression systems from prokaryotic E. coli [ 2 , 72 , 126 ] to eukaryotic systems such as yeast [ 17 ], insect cell/baculovirus systems (IC-BV) [ 38 , 67 ], mammalian cells [ 38 ], HSV-1 [ 90 ], and plant cells [ 37 , 89 , 127 ] have been used successfully to produce assembled structures of VP6 tubes/VLPs. ( B ) Applications of VP6 tubes/VLPs, as vaccines (immunogenicity and protection) [ 15 , 44 , 54 , 55 , 64 66 , 70 , 95 , 108 ], adjuvants [ 15 , 16 , 55 , 76 78 , 108 – 110 ], immunological carriers [ 49 , 53 , 92 , 96 , 102 , 111 ], drug delivery tools [ 5 , 91 , 122 , 126 ], and nano-biomaterials [ 5 , 23 , 24 , 41 , 42 , 50 , 91 , 122 , 126 ] …”
Section: Vp6 Expression and Formation Of Structured Vp6 Tubes/vlpsmentioning
confidence: 99%
“…1 B) [ 49 , 102 ]. Since then, there have been many reports on the successful application of RV VP6 structured protein assemblies for chimeric Ag delivery, including insertion of (i) a 14-amino-acid peptide derived from the simian paramyxovirus 5 (V5 epitope) by genetic fusion [ 96 ], (ii) three epitopes of poliovirus type 1 (PV1) [ 92 ], (iii) three epitopes derived from the VP4 of RV [ 114 ], (iv) two peptides (23 and 140 amino acids) derived from the M2 and hemagglutinin (HA) genes of influenza A virus [ 53 ], and, more recently, (v) insertion of the receptor-binding domain (RBD) of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) spike protein (S) to the surface loops or the N-terminus of VP6 without affecting protein conformation and immunogenicity [ 111 ]. The results of the immunization studies using these VP6-based chimeric Ag delivery systems in animal models have demonstrated the potency of VP6-based structured protein assemblies (VP6 tubes/VLPs) for induction of high titers of Abs and strong T-cell immune responses against both VP6 and the inserted Ag, suggesting the conformational conservation of both Ags in the chimera.…”
Section: Vp6 Tube/vlps As Immunological Carriersmentioning
confidence: 99%
“…Assembled VP6 has also been used as an immunological carrier, which first documented as heterologous peptides coupled to VP6 VLPs elicited excellent humoral responses . Several studies further support that homologous and heterologous epitopes genetically fused to VP6‐based platform could improve immune response to foreign epitopes . Among different VP6 preparations, assembled VP6s appear to be considered as a potential RV vaccine platform due to the ability to present conserved epitopes.…”
Section: Vp6 Immunogensmentioning
confidence: 99%
“…90,91 Several studies further support that homologous and heterologous epitopes genetically fused to VP6-based platform could improve immune response to foreign epitopes. [92][93][94] Among different VP6 preparations, assembled VP6s appear to be considered as a potential RV vaccine platform due to the ability to present conserved epitopes.…”
Section: Vp6 Dnamentioning
confidence: 99%